Characterization of parasitic residual deposition on passivation layer in electronics nickel immersion gold process - Mohd Khairuddin, Md Arshad; Azman, Jalar; Ibrahim, Ahmad (Elsevier Science, 2008)
Link to publisher's homepage at www.elsevier.com/locate/microrel